PKM PENINGKATAN DAYA SAING OLAHAN KERIPIK SINGKONG RASA JAMUR MELALUI PENGEMBANGAN KEMASAN DAN DIGITAL MARKETING DI DESA PETANANG PROGRAM KKN TEMATIK MBKM - Priandi, M. Ronal; Wijaya, Putra Oktri; Khalilly, Muhammad Naufal; Hertati, Lesi; Hendarmin, Rum; Syafitri, Lili; Munandar, Aris (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2022)
Petanang Village is one of 10 villages in the Lembak District. whose livelihood is as a farmer. The utilization of these agricultural products is a partner of the Community Partnership (PKM) program, especially processed from cassava into cassava chips whose packaging is still fairly unattractive. Digital Marketing is a promotional activity and market search through digital media online by utilizing various means, such as social networks. The virtual world is no longer only able to connect people with devices, but also people with other people around the world. Digital Marketing which usually consists of interactive and integrated marketing facilitates interaction between producers, market intermediaries, and potential consumers. The purpose of this service is to improve the quality and quantity of cassava chip processing through dissemination of packaging development, digital marketing and product logo creation, so that the output issued will be more attractive and of course will increase the profit of each cassava chip business actor in the Petanang village, Lembak sub-district.